Case series of trichotillomania presenting with three different DSM entities - Modi, Neha; Chaudhary, Pradhyuman; Mehta, Ritambhara; Dave, Kamlesh (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2021)
Trichotillomania (TTM; hair-pulling disorder) is classified as an obsessive-compulsive related condition within the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5). Trichotillomania affects 4% of the population with significant comorbidity (38.8%). It is found between trichotillomania and different DSM-5 entities such as schizophrenia, bipolar mood disorder or depressive disorders, obsessive-compulsive disorder, borderline personality disorder, obsessive-compulsive disorder (OCD) and with other body-focused repetitive behaviours (BFRBs) such as skin-picking disorder (SPD). We report three cases of trichotillomania with three different comorbid psychiatry disorders: schizophrenia, borderline personality disorder and bipolar mood disorder. Current treatment strategies for TTM involve a multimodal approach as according to research in the presence of comorbidity, treatment for TTM may need to be modified.